A TRAJETÓRIA DA REMUNERAÇÃO DOCENTE A PARTIR DAS POLÍTICAS PÚBLICAS EDUCACIONAIS E JURISPRUDÊNCIAS: ANÁLISE DAS DECISÕES DO SUPREMO TRIBUNAL FEDERAL - Ruth da Paz Camargo (2022)
This research entitled "The trajectory of teacher remuneration based on educational public policies and jurisprudence: analysis of the decisions of the Federal Supreme Court", inserted in the line of research teacher training and public policies, of the Master's course, of the Graduate Program in Education, from the Federal University of Mato Grosso do Sul, Três Lagoas Campus, has the general objective of analyzing the inference of the decisions of the Federal Supreme Court in the application of public policies for teacher remuneration. From this question, it is intended to understand the mechanisms of interpretation used by the judiciary in decisions regarding public policies for teacher remuneration; elucidate the competences of the federated entities regarding teaching remuneration and the right to education; to identify and understand the policies of funding funds for teacher remuneration and the right to education and to identify and analyze the inference of the decisions of the Federal Supreme Court in the application of public policies on teacher remuneration. Its relevance is justified due to the growing precariousness of education and the teaching profession, basic elements of the fundamental principles for a universal and quality education, as well as for the understanding that the remuneration of teachers is also linked to an emancipatory education, and that its conception comprises the combination of requirements, such as: remuneration, career, training and working conditions. In this work, the analysis of public policies for teacher remuneration will be carried out in the decisions of the STF, since the Floor Law cannot be recognized by the federated entities, despite being regulated at the federal level. This study made it possible to understand the judicialization as a way to ensure the effectiveness of public policies for teacher remuneration, despite the judiciary, nowadays, only ensuring the control of the payment of the minimum salary, causing the weakening of these public policies. Keywords: Public Policies. Education. Teacher Remuneration. Jurisprudence. Federal Court of Justice.